Sociobiology and Original Sin - Williams, Patricia A. (Zygon, 2000)
This paper argues that the creation narrative of the Fall in Genesis 2:4b–3:24 is not history and does not contain a doctrine of original sin. The doctrine of original sin as a theory of human nature needs a new foundation. The contemporary science of sociobiology has a theory of human nature that is remarkably similar to major versions of the Christian doctrines of original sin. To incorporate sociobiology's theory of human nature into Christianity is to lay the foundation for a new, ecumenical understanding of original sin.